The relationship between Dietary Inflammatory Index and disease severity and inflammatory status: a case–control study of COVID-19 patients. Issue 5 (14th March 2022) - Moludi, Jalal; Qaisar, Shaimaa A.; Alizadeh, Mohammad; Jafari Vayghan, Hamed; Naemi, Mohammad; Rahimi, Akram; Mousavi, Rihaneh
Abstract: Numerous studies have revealed strong relationships between COVID-19 and inflammation. However, the imminent link between diet-related inflammation and the COVID-19 risk has not been addressed before. So, we explored the capability of the Energy-Adjusted Dietary Inflammatory Index (E-DII) to predict the inflammatory markers, incidence and severity of COVID-19. We conducted a case-control study consisting of 120 adults; they had been admitted for COVID-19 at hospital during June and July, 2020. The E-DII score was calculated based on the dietary intake, which was evaluated by a 138-item semi-quantitative food frequency questionnaire. Serum levels of inflammatory markers including the Erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) and White blood cells (WBCs) differential were measured. Severity of disease was assessed by chest radiology criteria. Patients with the maximum pro-inflammatory energy adjusted E-DII score had 7·26 times greater odds of developing COVID-19, as compared to those in tertiles 1 (E-DII T3 v . E-DII T1 : OR = 7·26; 95 % CI 2·64 to 9·94, P < 0·001). Also, a positive association between E-DII and C-reactive protein (CRP) was observed (BE-DII = 1·37, 95 % CI 0·72, 2·02), such that with each unit increase in E-E-DII, the CRP levels were increased by 1·37 units. Furthermore, a significant association was found between E-DII and the severity of disease (BE-DII = 0·03, 95 % CI 0·01, 0·06. 0·024). Patients consuming a diet with a higher pro-inflammatory potential were at a greater risk of COVID-19 occurrence; also, the severity of disease was elevated with a high score inflammatory diet.